Predicting crack pattern on archimedes screw runner blade of micro hydro power - Ahmad Alif, Ahmad Adam (2013)
One of the fundamental studies of Micro hydro power with low head is the Archimedes screw runner. This research focuses on the study of behavior of fluid flow acting on the Archimedes screw runner blade and prediction of erosion pattern from fluid flow. The CAD model of the Archimedes screw blade was re-inversely design from past researcher. In order to determine the flow pattern, computational fluid dynamic, CFD was used to obtain the pressure distribution along blade structure. Analysis of three-dimensional with steady state flow was done with a standard k-ε as the turbulence model. The result obtained from pressure pattern shows that the highest value of coefficient of pressure obtained at the blade tip. This result shows that the prediction of crack may occur mostly at the blade tip. Further studies of blade design can be improved by reducing crack.